PENGARUH KUALITAS KEGIATAN MUSYAWARAH GURU MATA PELAJARAN (MGMP) TERHADAP PROFESIONALISME GURU EKONOMI PADA SMA NEGERI DI JAKARTA - Fidelina Herlin Rosavitri; Siti Nurjanah; Sri Indah Niken Sari (Fakultas Ekonomi Universitas Negeri Jakarta, 2012)
ABSTRACTThe Influence of Activity Quality Teacher Organization toward Economic Teachers Profesionalism at Public Senior High School in Jakarta.This research conducted to describe the activity quality teacher organization toward economic teachers profesionalism at public senior high school in Jakarta. This research was conducted during two months from May to June 2012. This research used survey method with the corelational approach. The observation using 20% from reach population to become sample. Data recording questionnaire are research technique. Before use, test the validity of the constructs (constructs validity) through a validation process is the calculation of correlation coefficient score points with the total score and the test of reliability with Cronbach alpha formula. Results instrument reliability variable X (Activity Quality teacher organization) of 0.919, while for variable Y ( teacher profesionalism) of 0.860. test requirements analysis is to find the regression equation obtained was Å¶ = 49.13 + 0.558 X. result of normality test resulted liliefors Laccount= 0.128 while for n=30, at the level of significance (Î± = 0.05) is 0.161. Because Laccount<Ltable the variables X and Y have normal distribution. Testing the hypothesis with the significance test of regression produces Faccount (14.12) >Ftable (4.12) which means significant regression equation. Linierity test F values of regression produce Faccount (-0.47) <Ftable (2.98) thus conclude that the linier regression equation. The result of product moment correlation coefficient produce rcalculate = 0.579. furthermore, the correlation coefficient significance test was done using t-test, resulting in taccount (3.76) > ttable (1.70). the result of product moment correlation coefficient quality teacher organization have positive and significant influence on the teacher profesionalism at public senior high school in Jakarta.Keyword : Activity quality teacher organization, teacher profesionalismshows tha the activity